Konsep Balanced Scorecard (BSC) dan Aplikasinya pada Organisasi Pendidikan - Rais Hidayat; Sulista Marwati; Aminullah Yasin (Jurnal Manajemen Pendidikan (JMP), 2019)
The success of an educational institution depends on the strategy set. The sharper the educational institution conducts a strategic analysis, the better the quality and image of the institution. Among the techniques in conducting a strategy study is to use the balanced scorecard method (BSC). In this article we present three main discussions: 1) the basic concept of balanced scorecard; 2) balanced scorecard in educational organizations; and 3) steps for implementing the balanced scorecard in educational organizations. This article uses literature studies sourced from scientific books and journals..keywords : balanced scorecard, management strategies, education organization